Designing Disaster Media Education For Children With Hearing Impairment In Special Education Center Banda Aceh - Nur Ikhsani Rahmatika; Zahrani Zahrani; Meilya SIlvalila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Banda Aceh, a coastal city located in the western most province of Indonesia, has long been known for its stunning natural beauty and vibrant cultural heritage. Situated on the northern tip of Sumatra Island, this bustling city is surrounded by the vast expanse of the Indian Ocean on one side and picturesque hills on the other. However, beneath its picturesque facade lies an alarming reality - Banda Aceh stands perilously exposed to a high risk of disaster.. With the history of disasters in Aceh which is one of the biggest disasters that has caused many casualties, education related to disaster awareness needs to be carried out. People with hearing disabilities are one of the vulnerable groups in the event of a disaster. Education related to disaster awareness is a form of non-structural mitigation which at this time has been widely carried out both in formal education in schools and campuses and informally in the community. Efforts to increase disaster awareness through education are important, including for groups with disabilities . As a group with hearing impairments, they are at greater risk when a disaster occurs because they cannot hear warnings through sound media and the communications gap. However, with disaster awareness through education, people with disabilities are also expected to be able to carry out independent evacuations and save themselves when a disaster occurs. This research aimed to explore the effectiveness of designing disaster media education for children with disabilities in Banda Aceh, Indonesia. Recognizing the unique vulnerabilities of children with disabilities during disasters, the study focused on developing an inclusive and accessible media-based educational program. The method used in the research is qualitative research and encompassed various stages, including needs assessment, program development and implementation. Designing disaster media education for children with disabilities in Banda Aceh proved to be an effective and essential approach to bridge the education gap and enhance disaster preparedness among this marginalized group. The research outcomes emphasize the importance of inclusive and accessible education in disaster management, aiming to ensure the safety and well-being of all children, regardless of their abilities. The findings of this research contribute to the growing body of knowledge on disability-inclusive disaster education and provide a basis for future program development and policy-making in disaster management in Banda Aceh and beyond.